Adaptive modes of adult men during COVID-19: qualitative analysis under Roy’s model - de Oliveira Muniz, Vinícius; Reis de Sousa, Anderson; da Silva Santana, Thiago; dos Anjos Santos, Alisson; Evangelista Luz, Ramon; Santos Almeida, Eric; Meira Araújo, Isabella Félix; de Santana Carvalho, Evanilda Souza (Investigación y Educación en Enfermería, 2023)
Objective. This study aims to understand how adult men adapt to the COVID-19 pandemic. Methods. Qualitative study involving 45 adult men residing in Brazil in 2020. Data were obtained from a Web Survey and treated using Reflective Thematic Analysis and interpreted in the light of Callista Roy’s Adaptation Model. Results. The COVID-19 pandemic mobilized in men the ways of adaptation that are configured in: mobilization of the physiological-physical and regulatory dimension: adjustments in the sleep pattern, dietary pattern, and maintenance of physical activity; group self-concept identity: managing emotions; role function: self-knowledge and self-care; interdependence: adjustments in the marital relationship, family ties and paternity, investment in training and studies and control of excessive consumption of content on cell phones. Conclusion. The perception of the own vulnerability favored the entry of men into ways of adaptation in search of balance during the pandemic, motivating them to move through practices of taking care of themselves and taking care of others. Markers of psycho-emotional distress alert to adherence to new modes of care capable of promoting healthy ransitions in the face of disruptions and uncertainties generated by the pandemic. This evidence can support the establishment of goals for nursing care aimed at men.